The Relationship between External and Internal Load during Elite Pre-season Friendly Basketball Games. [La relación entre la carga externa y la carga interna durante partidos amistosos en baloncesto de élite]. - Ruben Portes; Rafael Manuel Navarro; Carlos Ribas; Enrique Alonso; Sergio L. Jiménez (Ramón Cantó Alcaraz, 2022)
The aim of this study was to analyse the relationship between External Load (EL) and internal load (IL). Thirteen male basketball players competing at professional level in First Spanish Division (ACB) during six friendly games throughout the 2020/2021 preseason were monitored. The EL variables collected were movement load (ML), movement intensity (MI), box score time (BST), and total duration (TD)] while IL variables monitored were heart rate (HR), respiratory rate (RR), training impulse (TRIMP) and time invested in five HR zones. Very large to almost perfect correlation (r= 0.77-0.91) exists between EL variables except TD. In addition, HR, TRIMP and RR present large to very large correlation (r= 0.55-0.79) with all EL variables except TD. Monitoring HR-based variables would present general information and an estimated prediction of players EL which could allow basketball practitioners to prioritize time invested players internal/external load.